ADAMTS‐4 and ADAMTS‐5 expression in human temporomandibular joint discs with internal derangement, correlates with degeneration. (5th December 2014) - Leonardi, Rosalia; Crimi, Salvatore; Almeida, Luis Eduardo; Pannone, Giuseppe; Musumeci, Giuseppe; Castorina, Sergio; Rusu, Mugurel Constantin; Loreto, Carla
Abstract : Temporomandibular joint (TMJ) internal derangement (ID) is one of the most common form of temporomandibular disorders. There is evidence showing the increased expression of matrix metalloproteinases (MMPs) in the cells from degenerated TMJ disc. ADAMTS are a large family of metalloproteases which are responsible for proteoglycans degradation. The present study aimed to evaluate ADAMTS‐4 and ADAMTS‐5 immunohistochemical expression in human TMJ discs from patients affected by ID, and to find out if there is any correlation with the degree of histopathological changes. Eighteen temporomandibular displaced disc specimens and sixteen TMJ disc control were used for the present study. Specimens were immunohistochemically processed and ADAMTS‐4 and ADAMTS‐5 expression were obtained respectively for the anterior (AB), intermediate (IB) and posterior (PB) bands and compared to the histopathological degeneration score (HDS). Immunoreactivity for ADAMTS‐4 and ‐5, was observed in both not degenerated and degenerated human TMJ discs. Both the percentage of ADAMTS‐4 and ‐5 immunostained cells (ES) and the intensity of staining (IS) were significantly greater in affected specimens compared with those in control discs. The ADAMTS‐5 ES and IS of the 3 bands of the disc correlated to the TMJ disc HDS (0.001 < P  < 0.05), on the other hand only AB and IB, ADAMTS‐4 immunostaining scores correlated to HDS. According to these findings it can be assumed in that the more histopathological changes in the disc are detected, the higher levels of ADAMTS are produced. This in turn can lead to ECM breakdown and in turn to a more advanced disc displacement.